MATERIAL LONGSOR DAN CREEP MEMPENGARUHIAREA PERTANIAN DI SEKITAR DESA NGASINAN, PURWOREJO - purnamasari, Anastasia; Sartohadi, Junun; Hartantyo, Eddy (Jurnal Pertanian Agros, 2026)
The area around Ngasinan Village is hilly with thick soil. The hilly and thick soil conditions make the area prone to landslides. The landslide area intersects with the Ngasinan residents' agricultural land. Landslide material from large landslides and soil movement (creep) can affect agricultural land. This study aims to identify landslide and creep areas that impact agricultural land. The methods used were aerial photography, direct field observation, and in-depth interviews. Based on field data collection, it can be seen that several areas experienced soil movement (creep). Creep damaged irrigation embankments and disrupted agricultural land. Several large landslide locations collapsed thick material, causing the landslide material to press on agricultural land. The community reported that the landslide material did not significantly disrupt agricultural yields, although the boundaries of the rice fields changed. The results of this study can be the beginning of further research related to landslide material entering agricultural land. Then, it will be used as a consideration by the government in constructing irrigation embankments.